The study of the strength of dentures with different surface reliefs under the action of static loading - L. V. Kolomiets; V. F. Orobey; O. M. Lymarenko; Y. V. Ovcharov; O. V. Tsilvik (Medičnì Perspektivi)
The paper presents modeling of denture specimens with different surface reliefs under the action of static loading using modern numerical methods - finite and boundary elements. Based on the analysis of literature, it is shown that the most effective approaches for calculating the stress-strain state (SSS) of dentures is the finite element method (FEM), which allows you to create 3D models with any complexity of geometry and surface, as well as the boundary element method (BEM), which allows in some cases to obtain more accurate calculation results than finite element method. The algorithm and procedure for exact integration of differential equations of hollow shells according to the algorithm of Kantorovich-Vlasov variational method are presented for the formation of the calculated finite element method ratios. The analytical expressions for the parameters of the hollow shells used for calculations of the state of dentures are given. Finite element method is represented in the work by the universal package SolidWorks. Different stages of solid-state modeling of prototypes of dentures with different surface reliefs are shown in detail. Dental stress-strain state calculations were performed by two methods. The results of the calculations are in good agreement with each other, which proves the reliability of both models developed and the results of the stress-strain state received. It is shown that the smallest values of stresses occur in dentures with a rhombic lattice; they are 5.9% less than prosthesis with a smooth surface, and 18.78% less than in prosthesis with a square lattice. Equivalent displacement of a rhombic lath prosthesis is less by 3,864% than that of a smooth surface prosthesis and 8 52% less than a square lattice prosthesis.